Decaaqua-1 kappa O-5,4 kappa O-5-bis(mu-nitrilotriacetate)-1:2 kappa O-5:N,O `,O `',O `'';3:4 kappa N-5,O,O `,O `':O `''-mu-oxido-2:3 kappa O-2:O-diperoxido-2 kappa O-2,O `;3 kappa O-2,O `-1,4-dicopper(II)-2,3-dititanium(IV) heptahydrate - Xie, X.H.; Wang, B.M.; Ng, S.W. (International Union of Crystallography, 2010)
The tetranuclear title compound, [Cu2Ti2(C6H6NO6)(2)O(O-2)(2)(H2O)(10)]center dot 7H(2)O, lies about a twofold rotation axis that passes through the bridging oxide atom. The titanium atom is N,O,O',O `'-chelated by the nitrilotriacetate and O,O'-chelated by the peroidxo group and is coordinated to the bridging O atom in an overall pentagonal-bipyramidal geometry. The O atom of one of the carboxylate -CO2 groups binds to the water-coordinated Cu atom, whose coordination polyhedron is an elongated octahedron. Adjacent tetranuclear molecules are linked through the coordinated and uncoordinated water molecules by O-H center dot center dot center dot O hydrogen bonds into a three-dimensional network.